Compliment responses of Malay and Chinese in a Malaysian context: a case study / Siti Zaimaliza Masturi - Masturi, Siti Zaimaliza (2013)
This study explored the Malay’s and Chinese’s values and norms of the English compliments. This study aimed at studying the similarities and differences of the compliment response strategies employed by them. The similarities and differences were analyzed based on the Holmes (1988) compliment response strategies categories. From the qualitative and quantitative analysis conducted, the common linguistic features of the compliment responses structured by both races were then examined. Those are the three aims of this study which were achieved by taking the MSU students as the participants. Each respondent was given a discourse completion task (DCT) exercise and asked to write their responses based on the stated situations. Through the analysis carried out, it is revealed that the Malays and Chinese exhibited some similarities; it is observed that they tended to accept/reject the compliments on a personal achievement and belonging close to a person yet accepted or deflected/evaded the compliment on a skill. On the other hand, a few differences were also shown. It is revealed that the Malays and Chinese accepted the compliments on a job well done and a personal achievement respectively. Moreover, it is also examined that the Malays rejected the compliment on a personal achievement yet Chinese opted for the same strategy for the compliment on a belonging close to a person. Besides, it is also revealed that the Malays deflected/evaded the compliment on a non-personal item close to a person yet Chinese did the same for the compliment on a skill. From the analysis of the similarities and differences, three common linguistic features of the compliment responses were found; a variety of thank you was written when they opted for the appreciation token strategy, the word ‘no’ was chosen to indicate rejection and the word ‘really’ was used in expressing their deflection/evasion to the compliments. All these significant findings are beneficial to those who frequently engage in intercultural communications. In return, they will be able to hold conversations without fear of causing any misunderstandings and communication breakdowns especially when they take part in the act of complimenting with Malays and Chinese, since this study presents some socio cultural and pragmatic knowledge of the Malay and Chinese compliment responses.